Domestic military powers, law and human rights : calling out the armed forces - Head, Michael, 1952- (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"This book examines the national and international law, human rights and civil liberties issues involved in governments calling out the armed forces to deal with civil unrest or terrorism. The introduction of domestic military powers has become an international trend. Troops already have been seen on the streets in major Western democracies. These developments raise major political, constitutional and related problems. Examining the changes underway in eight comparable countries-the United States, Canada, Britain, France, Italy, Germany, Japan and Australia-this book provides a review and analysis of this trend, including its implications for legal and political rights. The book will be of interest to the general public, as well as students, academics and policy-makers in the areas of human rights and civil liberties, constitutional law, criminal justice and security studies"--
OCLC-licensed vendor bibliographic record.
Keywords: War and emergency powers; Civil-military relations; Armed Forces -- Mobilization; Human rights; LAW / General; LAW / Civil Rights; LAW / Comparative